Comparison of air exhausts for surgical body suits (space suits) and the potential for periprosthetic joint infection. Issue 3 (July 2018) - Ling, F.; Halabi, S.; Jones, C.
Summary: Background: Periprosthetic joint infection is a major complication of total joint replacement surgery and is associated with significant morbidity, mortality and financial burden. Surgical body suits (space suits), originally designed to reduce the incidence of infection, have paradoxically been implicated in increased periprosthetic joint infection rates recently. Air exhausted from space suits may contribute to this increased rate of periprosthetic joint infection. Aim: To investigate the flow of air exhausted from space suits commonly used in modern operating theatres. Methods: The exhaust airflow patterns of four commercially available space suit systems were compared using a fog machine and serial still photographs. Findings: The space suit systems tested all air exhausted into the operating room. The single fan systems with a standard surgical gown exhausted air laterally from the posterior gown fold at approximately the level of the surgical field. The single fan system with a dedicated zippered suit exhausted air at a level below the surgical field. The dual fan system exhausted air out of the top of the helmet at a level above the surgical field. Conclusions: Space suit systems currently in use in joint replacement surgery differ significantly from traditional body exhaust systems; rather than removing contaminated air from the operating environment, modern systems exhaust this air into the operating room, in some cases potentially towards the sterile instrument tray and the surgical field.